Muhammad: seal of the prophets - Syed Ali Ahsan; Muhammad Alamgir (A.S. Noordeen Kuala Lumpur, 2002)
"Muhammad: Seal of the Prophets" is a biographical account of the life of Prophet Muhammad, exploring his role as the final prophet in Islam and his profound impact on religion, society, and history.